2020
DOI: 10.1161/jaha.119.014333
|View full text |Cite
|
Sign up to set email alerts
|

FURIN Expression in Vascular Endothelial Cells Is Modulated by a Coronary Artery Disease–Associated Genetic Variant and Influences Monocyte Transendothelial Migration

Abstract: Background Genome‐wide association studies have shown an association between the single‐nucleotide polymorphism rs17514846 on chromosome 15q26.1 and coronary artery disease susceptibility. The underlying biological mechanism is, however, not fully understood. rs17514846 is located in the FES Upstream Region ( FURIN ) gene, which is expressed in vascular endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…The heart shows high levels of ACE2 , but low levels of TMPRSS2 expression, which calls into question the mechanism of injury and myocarditis observed in severe cases of COVID-19. However, a polybasic furin cleavage site has been recently identified in the SARS-CoV-2 spike protein [41] ; furin-like proteases that may contribute to SARS-CoV-2 spike protein processing are more ubiquitously expressed and may explain an expanded cell and tissue tropism of SARS-CoV-2 compared to SARS-CoV, which lacks this site [41] , [42] , [43] .
Fig.
…”
Section: The Sars-cov-2 Spike Protein and Ace2mentioning
confidence: 99%
“…The heart shows high levels of ACE2 , but low levels of TMPRSS2 expression, which calls into question the mechanism of injury and myocarditis observed in severe cases of COVID-19. However, a polybasic furin cleavage site has been recently identified in the SARS-CoV-2 spike protein [41] ; furin-like proteases that may contribute to SARS-CoV-2 spike protein processing are more ubiquitously expressed and may explain an expanded cell and tissue tropism of SARS-CoV-2 compared to SARS-CoV, which lacks this site [41] , [42] , [43] .
Fig.
…”
Section: The Sars-cov-2 Spike Protein and Ace2mentioning
confidence: 99%
“…Furin expression levels correlate with atherogenesis [157]. Recently, it has been revealed that expressed furin in vascular endothelial cells promotes the NF-κB activity; the expression of VCAM-1, MCP-1, and monocyte-endothelial adhesion; and transmigration [158], which results in further inflammation and damage of vascular endothelium. In addition to furin, vascular endothelium also highly expresses the ACE2 receptor [110] and the priming protease TMPRSS2 [159], which make the endothelium of patients with obesity highly susceptible to SARS-CoV-2 infection.…”
Section: Obesity and Endothelial Dysfunctionmentioning
confidence: 99%
“…For instance, the coronary artery disease genetic variant rs17514846 increases furin expression and this may be related to reduced monocyte migration and proliferation in humans [ 56 ]. Accordingly, the variant rs17514846 at the 15q26.1 locus was recently linked to higher circulating monocyte chemoattractant protein-1 (MCP-1) levels and greater carotid intima-media thickness in comparison with non-carrier individuals [ 57 ]. The same study also demonstrated that furin knockdown in vascular endothelial cells reduces endothelial cell-mediated inflammation as well as monocyte adhesion to and transmigration through these cells [ 57 ].…”
Section: Illness Degree and Association With Host Tissue Proteins mentioning
confidence: 99%
“…Accordingly, the variant rs17514846 at the 15q26.1 locus was recently linked to higher circulating monocyte chemoattractant protein-1 (MCP-1) levels and greater carotid intima-media thickness in comparison with non-carrier individuals [ 57 ]. The same study also demonstrated that furin knockdown in vascular endothelial cells reduces endothelial cell-mediated inflammation as well as monocyte adhesion to and transmigration through these cells [ 57 ]. A similar profile was observed in mice with atherosclerotic lesions treated with furin inhibitors (α-1-PDX, RP-070) [ 68 ].…”
Section: Illness Degree and Association With Host Tissue Proteins mentioning
confidence: 99%